1995
DOI: 10.1007/bf00209477
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of glucose-6-phosphate dehydrogenase (G6PD) deficiency in three Taiwan aboriginal tribes

Abstract: We have investigated glucose-6-phosphate dehydrogenase (G6PD) deficiency in 220 unrelated aboriginal male subjects who belong to three different tribes (Saisiat, Ami, and Yami) in Taiwan. Our results show that the G6PD deficiency rates for Saisiat, Ami, and Yami people are 9.0% (6/67), 6.1% (6/99), and 0% (0/54), respectively. Among these deficiency cases, 4 of 6 (66.7%) Saisiat subjects have the 493 A-->G mutation and one carries the 1376 G-->T mutation, whereas, in Ami subjects, we found that four of six (66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…G6PD Coimbra, which was first found in a Portuguese woman a Nucleotide change and amino acid change are G6PD Mahidol (487G>A, 163Gly>Ser), G6PD Coimbra (592C>T, 198Arg>Cys), G6PD Union (1360C>T, 454Arg>Cys), and G6PD Canton (1376G>T, 459Arg>Leu), respectively who lived in Coimbra, Portugal, is widely distributed in Europe and Asia but occurs with low frequencies (Corcoran et al 1992). In Asia, this variant is said to distribute among aborigines (Tang et al 1995). We found two cases of G6PD Coimbra among Malaysian aborigines (Iwai et al 2001) and four cases on Flores Island, Indonesia (Matsuoka et al 2003b).…”
Section: Resultsmentioning
confidence: 99%
“…G6PD Coimbra, which was first found in a Portuguese woman a Nucleotide change and amino acid change are G6PD Mahidol (487G>A, 163Gly>Ser), G6PD Coimbra (592C>T, 198Arg>Cys), G6PD Union (1360C>T, 454Arg>Cys), and G6PD Canton (1376G>T, 459Arg>Leu), respectively who lived in Coimbra, Portugal, is widely distributed in Europe and Asia but occurs with low frequencies (Corcoran et al 1992). In Asia, this variant is said to distribute among aborigines (Tang et al 1995). We found two cases of G6PD Coimbra among Malaysian aborigines (Iwai et al 2001) and four cases on Flores Island, Indonesia (Matsuoka et al 2003b).…”
Section: Resultsmentioning
confidence: 99%
“…G6PD activity from blood sam ples was analysed as described elsewhere [6,14]. De tection of known G6PD mutations commonly found in Chinese was performed as previously described (95, 487.1376. and 1388 mutations [15]; 493 mutation [6]; 392 and 1024 mutations [2]: 592 mutation [4]). …”
Section: Methodsmentioning
confidence: 99%
“…It may result in neonatal jaundice, drug-induced haemolytic anaemia, favism, and chronic nonspherocytic haemo lytic anaemia [1], The mutation type and occurrence rate of each G6PD mutation in the general population of Taiwan (including Chi nese and native Taiwan aborigines) have been reported recently [2][3][4], The frequency of G6PD deficiency in the Chinese population of Taiwan is 2-3% [5,6], and in three Taiwan aboriginal tribes (Saisiat, Ami, and Yami), is 9.0, 6.1, and 0%, respectively [4], We and others have recently shown that at least 12 different types of missense mutations, including 95 A->G [2,7], 392 G->T [8], 487 G -»A [6], 493 A->G [6], 592 C^T [4,9], 835 A->T [10], 871 G h>A [4], 1004 C^A [11], 1024 C->T [8], 1360 C->T [12], 1376 G ->T [13], and 1388 G h >A [13], are respon sible for G6PD deficiency in Chinese. Of these, the 1376 mutation is the most common allele, accounting for nearly 55% of deficiency cases in the Chinese population of Taiwan [2,3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the European and Middle Eastern populations, this is not in linkage disequilibrium with the C->T substitution at nt 1311. Glucose-6-phosphate dehydrogenase deficiency also occurs among the Chinese, and studies of allele frequency can be useful in determining migration and intermarriage patterns of the aboriginal tribes to Taiwan (38). The frequency of this disorder varies among the tribes: Saisiat, 9 percent; Ami, 6 percent; and Yami, 0 percent.…”
Section: Methods To Reduce the Bias In Allele Frequency Detectionmentioning
confidence: 99%